Plant disease diagnosis using deep transfer learning architectures- VGG19, MobileNetV2 and Inception-V3 - Kobra, Khadija-Tul; Suham, Rahmatul Rashid; Fairooz, Maisha (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.